Bagaimana manajemen tenaga pendidik pada Madrasah Ibtidaiyah Swasta? - Pratiwi, Tresiya; Kholid, Idham; Thahir, Andi; Dewi, Asmara (JOURNAL OF INTERDISCIPLINARY SCIENCE AND EDUCATION, 2021)
Educators are one of the vital aspects that control the continuity and success of teaching and learning activities in madrasas. With competent and professional educators, it is believed that the material taught will be quickly distributed to students. And because at the Madrasah Ibtidaiyah Working Group in Pringsewu there are still things that need to be improved, including that there are still no guidelines in the process of recruiting educators, so that the implementation of the recruitment of educators is still a lot of educators who teach not in accordance with their latest educational background. or not in accordance with their academic qualifications. The purpose of this study was to determine and understand the recruitment of educators who joined the Madrasah Ibtidaiyah Working Group in the Pringsewu Environment and to determine the placement of educators who joined the Madrasah Ibtidaiyah Working Group in the Pringsewu Environment.The method used in this research was a qualitative descriptive method. The data collection techniques using observation, interviews, and documentation. The results of the study indicate that the recruitment process for educators begins with planning for teacher needs, namely by analyzing existing needs, announcements of teacher vacancies, requirements that must be met by prospective teachers, selection and various tests, and determination of teacher acceptance. While the factors that become obstacles in the process of recruiting educators and placing educators are: the family system, lack of professionalism in implementing human resource management. Efforts made by madrasa heads in placing educators are done by placing educators who did not match their academic qualifications with the interests and talents of students in accordance with the positions given, and pay attention to the attitudes and appearances of prospective educators who will apply.